Relationship between Organizational Culture and Employee Performance through Work Stress at the Regional Office of the East Java I Directorate General of Customs - Komar, Irsan (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This study aims to analyze the Relationship between Organizational Culture and Employee Performance through Work Stress at the Regional Office of the Directorate General of Customs and Excise, East Java I. This research method is an explanatory research, the analysis unit in this study is employees who work in the Directorate General of Customs and Excise Office. East Java I region, which consists of 80 structural officials, 79 functional officials and 1323 executive staff. The method of collecting research data using a questionnaire. The results showed that organizational culture affects the work stress of employees at the Regional Office of the Directorate General of Customs and Excise, East Java I, this shows that organizational culture is able to increase the work stress of employees of the Regional Office of the Directorate General of Customs and Excise, East Java. Organizational culture influences the performance of the employees of the Regional Office of the Directorate General of Customs and Excise, East Java I, this shows that with a good and appropriate organizational culture, it is able to increase the performance of the employees of the Regional Office of the Directorate General of Customs and Excise, East Java I. New organizational culture that also improves Employee stress, namely the imposition of input into daily work activity reports by employees in the daily logbook through an internet-based application with details on the types of activities, time norms, achievement targets and employee daily problems for all levels of employees, both structural, functional and executive.